2008
DOI: 10.1002/sia.2718
|View full text |Cite
|
Sign up to set email alerts
|

Study of oxide protective layers on stainless steel by AES, EDS and XPS

Abstract: A protective oxide layer was formed on the surface of stainless steel by standard industrial-type thermal treatment. Additional post-thermal treatment annealing and polishing followed by annealing were applied in an attempt to improve characteristics of the layers. Oxide layers formed on samples without and with different types of post-thermal treatment processing were analysed and compared. Several techniques were employed. SEM was used to image the surface; AES, XPS and energydispersive spectroscopy (EDS) we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
28
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 8 publications
2
28
0
Order By: Relevance
“…The percentage of Fe in the scale decreases with increasing temperature and the formation of Cr-rich layer depends on the temperature. Mandrino et al [24] reported that Fe 3 O 4 starts to form throughout Cr 2 O 3 layer at temperatures above 950°C and the mixture of two oxide phases delayed the formation of Fe oxide. Therefore, the growth of Cr 2 O 3 becomes predominant and the concentration of Fe decreases by dilution effect.…”
Section: Resultsmentioning
confidence: 98%
“…The percentage of Fe in the scale decreases with increasing temperature and the formation of Cr-rich layer depends on the temperature. Mandrino et al [24] reported that Fe 3 O 4 starts to form throughout Cr 2 O 3 layer at temperatures above 950°C and the mixture of two oxide phases delayed the formation of Fe oxide. Therefore, the growth of Cr 2 O 3 becomes predominant and the concentration of Fe decreases by dilution effect.…”
Section: Resultsmentioning
confidence: 98%
“…The FWHM used for the metallic component was taken from the Cr and Fe peak measured after surface oxides were removed. The three and five oxides peaks, respectively, were expected to be present based on previous works [10,14,[38][39][40][41][42]. Fig.…”
Section: Methodsmentioning
confidence: 91%
“…In previous work [2] with passivated A-286, titanium was found at the surface in concentrations exceeding its bulk composition. Otherwise though, the A-286 depth profile [2] appears qualitatively similar to those seen in 300 series stainless steels [2,[4][5][6][7][8][9], with an adventitious carbon layer that is gradually sputtered away and an oxide layer that is indicative of the passivated layer [2,[4][5][6][7][8][9]. Previously, the oxide layer seen in A-286 was 4 nm [2].…”
mentioning
confidence: 84%
“…Previously, the oxide layer seen in A-286 was 4 nm [2]. The oxide layers for untreated 300 series stainless steels ranged from 1 to 3.5 nm [4][5][6], while the oxide layer for specially treated 300 series stainless steels ranged from 25 nm to 2 microns thick [5][6][7][8]. Scanning electron microscopy (SEM) images from the 300 series stainless steels show a relatively smooth and flat untreated surface [4][5][6], except in reference [7], which shows a relatively rough surface for the untreated stainless steel.…”
mentioning
confidence: 93%
See 1 more Smart Citation